The differing biogeochemical and microbial signatures of glaciers and rock glaciers. Issue 3 (29th March 2016) - Fegel, Timothy S.; Baron, Jill S.; Fountain, Andrew G.; Johnson, Gunnar F.; Hall, Ed K.
Abstract: Glaciers and rock glaciers supply water and bioavailable nutrients to headwater mountain lakes and streams across all regions of the American West. Here we present a comparative study of the metal, nutrient, and microbial characteristics of glacial and rock glacial influence on headwater ecosystems in three mountain ranges of the contiguous U.S.: the Cascade Mountains, Rocky Mountains, and Sierra Nevada. Several meltwater characteristics (water temperature, conductivity, pH, metals, nutrients, complexity of dissolved organic matter (DOM), and bacterial richness and diversity) differed significantly between glacier and rock glacier meltwaters, while other characteristics (Ca 2+, Fe 3+, SiO2 concentrations, reactive nitrogen, and microbial processing of DOM) showed distinct trends between mountain ranges regardless of meltwater source. Some characteristics were affected both by glacier type and mountain range (e.g., temperature, ammonium (NH4 + ) and nitrate (NO3 − ) concentrations, and bacterial diversity). Due to the ubiquity of rock glaciers and the accelerating loss of the low‐latitude glaciers, our results point to the important and changing influence that these frozen features place on headwater ecosystems. Key Points: Rock glacier meltwaters have higher metal concentrations than glacier meltwaters Organic matter composition differs between glacier types Microbial diversity is higher in rock glaciers than glaciers